Characteristic TARC/CCL17 expression in the salivary gland of IgG4-related disease: potential diagnostic utility and insights into pathogenesis - Nanako Kikuchi; Sae Hatanaka; Terufumi Kubo; Ryuta Kamekura; Masatoshi Kanda; Takuya Kakuki; Takashi Sasaya; Kengo Mita; Hiroki Kobayashi; Hajime Ikai; Kenta Sasaki; Naoki Shijubou; et al. (Immunological Medicine)
Immunoglobulin G4-related disease (IgG4-RD) is a chronic inflammatory condition of unknown etiology characterized by lymphocytic infiltration, fibrosis, and infiltration of IgG4-positive plasma cells. It affects various organs, including the pancreas and salivary glands. Immunological abnormalities are suspected to play a role in its pathogenesis, and there is an epidemiological link to allergic conditions and type 2 inflammation. This study focused on the expression of thymus and activation-regulated chemokine (TARC)/CCL17, which is involved in the migration of T helper 2 and/or regulatory T cells, in salivary gland tissues of patients with IgG4-RD. We analyzed 60 salivary gland biopsy samples obtained from patients at Sapporo Medical University Hospital between 2015 and 2020. Immunohistochemical analysis revealed TARC/CCL17 positivity in 87.2% of histologically confirmed IgG4-RD cases and negativity in 84.6% of histologically unconfirmed but clinically suspected IgG4-RD cases. There was a significant correlation between histologically confirmed IgG4-RD and TARC/CCL17 expression, suggesting its potential diagnostic utility and possible involvement in the pathogenesis of IgG4-RD.